FOXO3a‐mediated long non‐coding RNA LINC00261 resists cardiomyocyte hypoxia/reoxygenation injury via targeting miR23b‐3p/NRF2 axis. Issue 15 (18th June 2020) - Zhang, Ruining; Li, Yongjun; Liu, Xiaopeng; Qin, Shan; Guo, Bingyan; Chang, Liang; Huang, Liu; Liu, Suyun
Abstract: Ischemia/reperfusion (I/R)‐mediated acute myocardial infarction (AMI) is a major pathological factor implicated in the progression of ischemic heart disease (IHD). Long non‐coding RNA plays an important role in regulating the occurrence and development of cardiovascular disease. The aim of this study was to investigate the regulating role of LINC00261 in hypoxia/reoxygenation (H/R)‐induced cardiomyocyte apoptosis. The relative expression of LINC00261, miR‐23b‐3p and NRF2 were determined in rats I/R myocardial tissues and H/R‐induced cardiomyocytes. The rat model and cell model of LINC00261 overexpression were established to investigate the biological function of LINC00261 on H9C2 cell. The interaction between LINC00261, miR‐23b‐3p, NRF2 and FOXO3a was identified using bioinformatics analysis, luciferase reporter assay, RNA immunoprecipitation (RIP) assay, chromatin immunoprecipitation (CHIP) assay and qRT‐PCR. The expression of LINC00261 was significantly down‐regulated in myocardial tissues and H9C2 cell. Overexpression of LINC00261 improves cardiac function and reduces myocardium apoptosis. Interestingly, transcription factor FOXO3a was found to promote LINC00261 transcription. Moreover, LINC00261 was confirmed as a spong of miR23b‐3p and thereby positively regulates NRF2 expression in cardiomyocytes. Our findings reveal a novel role for LINC00261 in regulating H/R cardiomyocyte apoptosis and the potency of the LINC00261/miR‐23b‐3p/NRF2 axis as a therapeutic target for the treatment of MIRI.